Anhuienoside C Ameliorates Collagen-Induced Arthritis through Inhibition of MAPK and NF-κB Signaling Pathways - Liu, Qing; Xiao, Xu-Hui; Hu, Liu-Bing; Jie, Hui-Yang; Wang, Ying; Ye, Wen-Cai; Li, Man-Mei; Liu, Zhong (Frontiers in Pharmacology, 2017)
Anemone flaccida Fr. Schmidt (Ranunculaceae) (Di Wu in Chinese) is used to treat punch injuries and rheumatoid arthritis (RA). Our previous report has shown that crude triterpenoid saponins from A. ﬂaccida exhibited anti-arthritic effects on type II collagen-induced arthritis in rats. Furthermore, anhuienoside C (AC), a saponin compound isolated from A. ﬂaccida, was observed to suppress the nitric oxide (NO) production in lipopolysaccharide (LPS)-treated macrophage RAW 264.7 cells. In this study, we examined the effects of AC on the prevention and treatment of collagen-induced arthritis in a mouse model and evaluated the potential mechanisms involved. We observed that oral administration of AC significantly suppressed the paw swelling and arthritic score, descreased the body weight loss, and decreased the spleen index. Improvement in the disease severity was accompanied by the reduction of cluster of differentiation 68 (CD68)-positive cells in the ankle joint and inhibition of the proinflammatory cytokine tumor necrosis factor alpha (TNF-α) in the synovium of the joint. Mechanistic studies indicated that AC exerted its anti-inflammatory activity by inhibiting the mRNA expression levels of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), TNF-α, interleukin (IL)-1β, and IL-6 and by suppressing the production of inflammatory cytokines such as TNF-α, IL-1β, and IL-6 in LPS-treated RAW 264.7 cells. AC also blocked the LPS-induced activation of the extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 mitogen-activated protein kinase pathways. Additionally, the LPS-induced activation of nuclear factor kappa-B (NF-κB) was significantly suppressed by AC treatment, as indicated by down-regulation of TLR4 and inhibition of the nuclear translocation of NF-κB p65 and by activation and degradation of the inhibitor of kappa B (IκBα). These findings indicated that AC has a great potential to be developed as a therapeutic agent for human RA.